Characterization of the CZTS (Cu2ZnSnS4) thin film for solar cell absorber layer synthesized from the nitrate-based sol-gel precursor solution - Rahman, M; Bashar, MS; Islam, N (Dhaka University Journal of Applied Science and Engineering, 2023)
Manufacture of eco-friendly CZTS (Cu2ZnSnS4) thin film absorption layer of pure keserite structure for solar cell is far-reaching. We have manufactured the CZTS thin films by sol-gel dip-coating means from the nitrate-based chemicals. After hardening at 550°C in vacuum condition, we characterize the films by UV–vis spectroscopy, X-ray diffraction (XRD), Scanning Electron Microscope (SEM), and energy dispersive X-ray spectroscopy (EDS) methods. The CZTS films provided high optical absorption coefficient (2.92x104cm-1) and average band gap energy (1.58 eV). X-ray diffraction analysis proved the kesterite structure of films. The surface morphology analysis proved the deposition of crammed, condensed and granulated CZTS films. The thin films have intermittent disposal of agglomerated particles with clear-cut edges. The energy dispersive X-ray spectroscopy analysis conferred stoichiometric ratio as Cu: Zn: Sn: S= 2.1: 1.3: 1: 5.2. DUJASE Vol. 7 (2) 1-7, 2022 (July)